Grant Activities and Sustainability of Higher Education Institutions: Evidence from Russia - D. A. Endovitsky; V. V. Korotkikh; E. Y. Bubnova (Высшее образование в России)
This paper presents the results of a quantitative analysis of the contribution of grant activities to ensuring the sustainable development of higher education institutions in the Russian Federation. The authors consider sustainability in five aspects of activity: educational, research, international, financial and social. Results of higher educational institutions performance monitoring (2014-2022) formed the empirical basis of the study. In this research, we used the quantile regression model to identify the effects of inertial development and the effects associated with grant activities in the dynamics of universities performance indicators. We estimated the model parameters separately in each of the decile groups. Thus, we tested the central hypothesis of the study about the quantile heterogeneity of the sensitivity of university target indicators to the intensity and effectiveness of grant funding. This paper provides evidence of significant contributions the inertial nature of the development of universities, representing advanced development groups, into the sustainability of target performance indicators. However, in terms of sensitivity to the effectiveness and intensity of grant activities, they are inferior to universities from catch-up development groups in almost all aspects of their activities. The identified patterns of sensitivity to grant funding indicate a high potential for convergence (“catch-up development effect”) in the higher education system of the Russian Federation. These patterns can improve the effectiveness of management decisions in higher education by focusing on growth points with high sensitivity to grant support.